Problematika Pembelajaran Online di Masa Pandemi Covid-19 - Nicky Rosadi (Neolectura, 2021)
This study aims to analyze the problems of online learning during the Covid-19 pandemic. The methods used in this research are ex post facto and survey methods. The result is that online learning is not about what applications teachers use to teach their students. Teachers should not be busy debating which platform is better than another. However, teachers should realize that the most important thing is to apply teaching principles. Teaching is a process of making someone who doesn't know knows. The interaction between teachers and students is the key to conveying information. This information delivery room must be appropriate and easily accessible so that meetings between teachers and students can occur and give birth to neat and good interactions. In other words, a virtual study room must be highly accessible. In addition, the delivery of this interaction also needs to be arranged in such a way that students do not feel forced or forced to